Highlighting the Possible Causes of Health Disorders in Stored Yam at Farm Gate in Ghana - Moomin Abu; Kwara Francis Adzigiwe (Research Highlights in Agricultural Sciences Vol. 1, 2022)
Yams are herbaceous, climbing, twining, perennial monocots; they are the starchy, tuberous root of any of the various climbing vines of the genus Dioscorea cultivated or occurring naturally in warm regions. A survey was carried out in some selected major yam producing areas in the Nanumba North District of Ghana to investigate possible cause(s) of yam health disorders while in storage at farm gate. The objective was to obtain first hand information for further investigation(s) toward improving shelf life and quality of yam for export and local markets. Simple random sampling technique was used to select five communities and hundred respondents. A mixed method research design was used for data collection via the application of Participatory Research Appraisal tools and techniques. Personal communications and observations, and focus group discussions were also employed. Data was analysed quantitatively using descriptive statistics via SAS software. Ages of respondents (all males) were in the range of 11 to over 60 years with illiterate majority. Twelve (12) cultivars Laribako, Limo, Fuseini, Prinjo, Nawari (water yam), Alando, Akaba, Baatoo, Nyame-Nti, Afayili, Baffoo, and Pona were discovered with Laribako, Fuseini, Alando, Prinjo, and Nawari being the most widely cultivated, either alone or in combination with other cultivars on the same plot. Respondents were inadequate in agronomic, harvest, and postharvest practices and technologies necessary prior to storage. Storage structures included “in situ”, barns, wooden platforms, shallow trenches, ashes in packages, and pyramidal piles. Incidences of pests and diseases occurrences on yam fields were reported. Causes of yam health concerns and associated problems in store were termites, rats, mealybugs, rodents, weed pests, tuber rot, yam beetles, snakes, scorpions, including poor state of storage structures. Research, government, and other stakeholder institutions should partner up and make improved and certified yam sets accessible and affordable. Intensified agriculture extension services’ interventions should be enforced to empower farmers on agronomic, harvest, and postharvest practices and technologies.